Debt To Asset Ratio, Debt To Equity Ratio, Return On Asset, Return On Equity, Net Profit Margin And The Effect On Stock Prices In Indonesia Energy Sector Companies - Sunarsih, Meida Dwi; Misdiyono, Misdiyono; Nugraheni, Titi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Abstract: The purpose of this study is to analyze the effect of Debt to Asset Ratio, Debt to Equity Ratio, Return On Asset, Return on Equity, and Net Profit Margin on stock prices, especially in energy sector companies in Indonesia. The data analysis methods used are descriptive statistical tests, classical assumption tests, multiple linear regression analysis tests, T-tests, F-tests, and determination coefficient tests. The sample in this study was 20 energy sector companies listed on the Bursa Efek Indonesia ( BEI ) during the 2017-2021 period and met the sample selection criteria. The sampling technique used was Purposive Sampling. The data used is secondary data obtained from the company's financial statements. The results of the study indicate that Return On Asset has a partial effect on stock prices while Debt to Asset Ratio, Debt to Equity Ratio, Return On Asset, Return on Equity, and Net Profit Margin do not affect stock prices in energy sector companies in Indonesia. Keywords Debt to Asset Ratio, Debt to Equity Ratio, Return on Assets, Return on Equity, Net Profit Margin, and Share Price